PREDIKSI PENJUALAN DISTRIBUTOR CV. LESTARI MANDIRI JAYA MENGGUNAKAN METODE FUZZY MAMDANI - Seven, Sevrius Ndruru; Koko Handoko (Computer Science and Industrial Engineering, 2024)
Distribution firms frequently encounter difficulties in forecasting distributor sales due to the absence of a well-organized and precise prediction system. Inaccurate sales forecasts can result in issues that disturb business operations. The objective of this study is to identify sales data variables through fuzzy Mamdani calculations to forecast distributor sales for the company. To solve the sales prediction challenge, this research utilizes MATLAB software. Numerical data is vital in data processing as the fuzzy Mamdani logic method necessitates numerical data for processing in MATLAB. Once the data conversion process is finished, the subsequent step is to implement it in MATLAB to derive research findings that involve input and output variables. Tests were performed using two approaches: manual calculations and MATLAB. In every test, both manual and MATLAB methods were employed for defuzzification. The findings from both methods showed a sales increase with the same value of 85, indicating consistency between the methods and validating the accuracy of the implemented fuzzy model. Utilizing the fuzzy Mamdani method and MATLAB implementation allows companies to forecast distributor sales with greater precision. This analysis assists companies in recognizing sales trends and developing effective strategies to boost distributor sales.